Two new species of Hampala from Borneo (Teleostei: Cyprinidae) - Tan, Heok Hui; Jongkar, Grinang (Lee Kong Chian Natural History Museum, National University of Singapore, 2025)
Two new species of Hampala are described from Borneo Island. Hampala lupar, new species, is closely allied to H. bimaculata but differs in having three black bars on the body, vs. two bars; with the additional black bar just posterior to head. Hampala lupar is distinguished from all congeners by the following combination of characters: lateral line scales 26–27; three black bars on body, even at juvenile stage; upper and lower edges of caudal fin with a black marginal stripe; all fins orange with caudal fin reddish-orange when alive. Hampala katibas, new species, is similar to H. bimaculata but differs in having two large black blotches on the body, vs. two curved black bars; amongst other characters. Both new species are separated by the Lupar Geological Divide.